Implementasi Pendekatan Saintifik Sebagai Pembentuk Keterampilan Proses Sains Anak Usia Dini - Maria Melita Rahardjo (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2019)
Science education for early childhood education has received considerable attention from many researchers. Even though the new Indonesian early childhood curriculum does not provide specific curriculum objectives for science lesson, the science has been integrated in the curriculum through ‘pendekatan saintifik’ (scientific approach). There are not many journal articles which covered this topic. Several journals mentioned the importance of this approach, some other journals tried to find best model for implementing the approach. However, very few journals discussed deeply about the implementation of that approach. Therefore, this research paper will discuss the findings of scientific approach in three early childhood schools. The descriptive qualitative approach was used in the research.. The results show that the time allocation, the number of objects provided, and teachers’ questions are three important factors which affect the quality of scientific approach implementation.